2009
DOI: 10.1161/hypertensionaha.108.123406
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone and Metabolic Dysfunction

Abstract: A large body of evidence suggests that aldosterone excess is a common cause of hypertension with a prevalence of primary aldosteronism (PA) of Ϸ10% in patients with mildto-moderate hypertension and Ϸ20% in patients with resistant hypertension. 1 Experimental and clinical data also demonstrate that aldosterone excess contributes importantly to the development and progression of cardiorenal disease. This effect is attributed in part to aldosterone-induced target organ inflammation and fibrosis. Separately, a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
0
11
1
3
Order By: Relevance
“…24 The link between elevated plasma aldosterone levels and the metabolic syndrome and its single components, especially abdominal obesity, although rather extensively evaluated, is still controversial. [25][26][27] In spite of failing to reveal, as another study also did, 8 any correlation between PAC or ARR and spironolactone response, we demonstrated that a higher waist circumference was one of the predictors of a greater SBP reduction after spironolactone use, thus supporting the relationship between obesity and potential aldosterone excess.…”
Section: Discussioncontrasting
confidence: 53%
“…24 The link between elevated plasma aldosterone levels and the metabolic syndrome and its single components, especially abdominal obesity, although rather extensively evaluated, is still controversial. [25][26][27] In spite of failing to reveal, as another study also did, 8 any correlation between PAC or ARR and spironolactone response, we demonstrated that a higher waist circumference was one of the predictors of a greater SBP reduction after spironolactone use, thus supporting the relationship between obesity and potential aldosterone excess.…”
Section: Discussioncontrasting
confidence: 53%
“…1 Indeed, aldosterone is not only linked to systemic inflammation, endothelial dysfunction, increased vascular stiffness, hypertension, and cardiac hypertrophy, but also to impaired pancreatic β cell function, skeletal muscle insulin sensitivity, liver deficiency, and increased release of proinflammatory cytokines from adipose tissue leading to impaired glucose tolerance and dyslipidemia. [1][2][3] The cause of the apparent hyperaldosteronism induced by obesity is, however, unknown. Neither angiotensin II (AngII), nor plasma potassium (K + ) or adrenocorticotropic hormone, the 3 main regulators of aldosterone secretion, 4 contribute to the inappropriately high aldosterone levels observed in obese patients.…”
mentioning
confidence: 99%
“…We appreciate the editorial comments by Pimenta and Calhoun 1 and the correspondence by Sechi et al 2 on our work. Attempts to clarify the discrepancies between available studies on the metabolic effects of hyperaldosteronism are welcome.…”
mentioning
confidence: 77%